Video streaming over Ad hoc on-demand distance vector routing protocol - Othman O. Khalifa; Diaa Eldin Mustafa Ahmed; Aisha Hassan Abdalla Hashim; Mudathir Yagoub (Bulletin of Electrical Engineering and Informatics, 2019)
Video streaming is content sent in compressed form over the netwoks and viwed the users progressively. The transmission of video with the end goal that it can be prepared as consistent and nonstop stream. The point is that to give client support to client at anyplace and at whatever time. Mobile Ad hoc Networks (MANETs) are considered an attractive nertwork for information transmission in many applications where the customer programme can begin showing the information before the whole record has been transmitted. Ad hoc On-demand Distance Vector (AODV) protocol is considered as one of the most important routing protocols in MANET. However, routing protocols assume a crucial part in transmission of information over the network. This paper investigates the performance of AODV Routing Protocol under video traffic over PHY IEEE 802.11g. The protocol model was developed in OPNET. Different outcomes from simulation based models are analyzed and appropriate reasons are also discussed. A different scenarios of video streaming were used. The metric in terms of throughput, end to end delay, packet delivery ratio and routing overhead were measured. A comparision with GRP and GRP are also reported.